Pengaruh Pdb Adhk, Inflasi, Jumlah Pengangguran Terhadap Kemiskinan Di Indonesia - saffana, wanda aulia (LPPM Universitas Muhammadiyah Mamuju, 2023)
Poverty is a fundamental problem that is the center of attention of the government in any country. Poverty is usually caused by the national conditions of a country and the global situation. This research is to analyze the influence of ADHK GRDP, inflation, population on poverty in Indonesia from 1989 – 2019. The data used in this research is secondary data sourced from the Central Bureau of Statistics (BPS). This study uses a variable analysis tool using the ECM causality model. Based on the results of data analysis, it shows that the GDP ADHK variable has no significant effect on poverty, while inflation and population have a significant effect on poverty in Indonesia in 1989 - 2019.